RETURNING A CRIMINAL CASE TO THE PROSECUTOR AND BALANCING PUBLIC AND PRIVATE INTERESTS - ZAYTSEVA Elena Aleksandrovna (Правовое государство: теория и практика)
Criminal proceedings, being public by their nature, require in civilised states a balance between public and private interests. The approaches of the Constitutional Court of the Russian Federation to determining this balance are not always accurately embodied by the legislator in newly adopted criminal procedural norms. In recent years, there has been a gradual strengthening of public principles and narrowing of the sphere of private interest in a number of institutions of criminal procedure law. This is illustrated by the legal institution of returning a criminal case to the prosecutor. Purpose: to analyse the norms of the legal institution of returning a criminal case to the prosecutor through the prism of the balance of private and public interests. Methods: comparative-legal, historical, legal-dogmatic and interpretation of legal norms. Results: the study allows to substantiate the thesis that the balance of private and public principles in criminal proceedings is a very mobile “substance”, which is under the influence of constantly developing social relations (objective factor) and requests of ruling elites (subjective factor); the article reveals the main trends in the establishment of this balance in the system of norms of the legal institution of returning a criminal case to the prosecutor.